The Idea of Jurisdictional Representation in a Federation: A Proposal and Illustrations from Recent Canadian and US Elections - Syed M. Ahsan (Center for Economic Studies and Ifo Institute (CESifo), 2020)
The idea of proportional representation has been circulating for over two hundred years and is widely practiced, among other, in post-war Europe. The primary focus is to allow smaller parties, minorities and other disenfranchised groups in society systematic representation in the national legislature. This paper proposes a novel idea of jurisdictional-level proportionality specifically targeted at federal systems. Emphasising the primacy of jurisdictions (namely provinces and states) within a federation, we use data on the voting pattern in each such jurisdiction to determine the allocation of elected delegates (or electoral seats for that matter) that would be utilized in the eventual makeup of the ruling government. The proposed scheme is the simplest that we know of. All it requires is the record of all votes cast by individuals in favour of the candidate of their choice in a given constituency. Our design ensures that the mechanism encompass the governance virtues such as (a) inclusivity and stability of the elected government, (b) accountability of elected delegates and their interface with voters, and (c) and fully conform to the principle of proportionality. In the parliamentary mode, while it may tend to predict minority governments more often, it allows each major party a greater degree of freedom to forge a ruling coalition. When reviewing the US Presidential election, it appears that the outcome here may change too, typically in favour of the plurality winner of nation-wide popular votes, even though the seat arithmetic is based on proportional votes within each state in the union.
Keywords: D72; H77; I31; 330; the agency problem; effective governance; gerrymandering; inclusive representation; jurisdictional representation; proportional representation; stable government